2021
DOI: 10.1111/jpc.15421
|View full text |Cite
|
Sign up to set email alerts
|

Brain death in a child as a result of COVID‐19‐associated acute stroke: The first case

Abstract: Cerebrovascular events associated with COVID-19 may be due to systemic inflammation and hypercoagulable state resulting from cytokine storm, post-infectious immune-mediated response and direct viral-induced endotheliitis or endotheliopathy. 1,2 The reported incidence of stroke in COVID-19-hospitalised patients is 1.3-2.4%, 3,4 and young adult patients in their 30s are also reported to have COVID-19-related stroke. 5,6 Recently published case series and case reports revealed thromboembolic events in adult patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…He improved and was discharged with moderate disability. Kanğın et al [13] reported a case of a seven-year-old previously healthy child with COVID-19 infection and catastrophic intracranial arterial thromboembolic event leading to brain death.…”
Section: Discussionmentioning
confidence: 99%
“…He improved and was discharged with moderate disability. Kanğın et al [13] reported a case of a seven-year-old previously healthy child with COVID-19 infection and catastrophic intracranial arterial thromboembolic event leading to brain death.…”
Section: Discussionmentioning
confidence: 99%
“…In a case series report from Chile 2021, the neurologic complications were epilepsy exacerbation, anosmia, ageusia, headache, Guillain-Barre syndrome, encephalopathy, and demyelinating events (14). A case of stroke firstly resulted in brain infarction and death in a child with COVID-19 (15). The pathophysiology of acute cerebral ischemia in COVID-19 are para-infectious and immune-mediated, and hypercoagulable state and endothelial indentation (15).…”
Section: Discussionmentioning
confidence: 99%
“…A case of stroke firstly resulted in brain infarction and death in a child with COVID-19 (15). The pathophysiology of acute cerebral ischemia in COVID-19 are para-infectious and immune-mediated, and hypercoagulable state and endothelial indentation (15). The virus interferes with the function of ACE2 in cerebrovascular self-regulation, while reports of thrombosis, especially in the higher ages, have been reported (16).…”
Section: Discussionmentioning
confidence: 99%